2021
DOI: 10.1097/phh.0000000000001351
|View full text |Cite
|
Sign up to set email alerts
|

College Students' Experiences of Race-Related Bias or Hatred in Their Lifetimes and COVID-19 Era

Abstract: Objective:The primary aim of this study was to investigate whether students in minority race categories are more likely to experience race-related bias and hatred in their lifetime and since the onset of COVID-19, after controlling the effect of demographic and other variables. Methods: This quantitative study used primary data from the survey of 1249 college students at one of the universities in Georgia during April and May 2020. We performed multinomial logistic regression, computing 2 models for the 2 ordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
(67 reference statements)
0
5
0
Order By: Relevance
“…Few studies have also been able to examine how the pandemic may affect changes in attachment. Furthermore, several studies have demonstrated that, rather than the expected increase in mental health risks during the pandemic, there is significant variability with many young adults not experiencing mental health problems (e.g., Cost et al, 2021 ; Shanahan et al, 2020 ) while some ethnic groups may experience more and worsened mental health concerns (e.g., Shah et al, 2021 ), underscoring the importance of addressing ethnic group differences.…”
Section: Development Of Attachment To Parents and Peersmentioning
confidence: 99%
See 2 more Smart Citations
“…Few studies have also been able to examine how the pandemic may affect changes in attachment. Furthermore, several studies have demonstrated that, rather than the expected increase in mental health risks during the pandemic, there is significant variability with many young adults not experiencing mental health problems (e.g., Cost et al, 2021 ; Shanahan et al, 2020 ) while some ethnic groups may experience more and worsened mental health concerns (e.g., Shah et al, 2021 ), underscoring the importance of addressing ethnic group differences.…”
Section: Development Of Attachment To Parents and Peersmentioning
confidence: 99%
“…Asian Americans were found to experience equivalent levels of mental health problems as other ethnic groups, with perceived and experienced racial discrimination being one of the main contributors (e,g., Hwang & Goto, 2008 ). During the COVID-19 pandemic, Asians have been targeted even more with reported anti-Asian hatred and crime (e.g., Shah et al, 2021 ). Moreover, Asian American’s wellbeing has been found to be positively impacted by attachment to parents and peers (e.g., Ying & Lee, 2007 ; Han & Lee, 2011 ).…”
Section: Development Of Attachment To Parents and Peersmentioning
confidence: 99%
See 1 more Smart Citation
“…Health equity in the United States became a more critical issue during the COVID-19 pandemic because it magnified historical disadvantages among populations typically at a higher risk of poor health outcomes due to social, cultural, and structural barriers to scientific information, adequate housing, wraparound services (support services for individuals receiving medical or public health services) for those affected, and preventive care. 10,46 The study provides examples of best practices for health departments from their peers’ health equity activities. The results show that accreditation of public health agencies plays a central role in mobilizing state and local health departments to support a culture of health equity.…”
Section: Studies Using Data Generated By Public Health Practitioners ...mentioning
confidence: 99%
“…Interestingly, Ji and Chen (2022) indicated that the Chinese international students not only felt stigmatized by the majority in the US, but also felt blamed and received less support from the Chinese back in China, as they were told it was their own choice and responsibility for leaving China and studying in the US. Moreover, self-stigma during the pandemic was not limited to Asians per se, as other ethnic minorities also reported higher experiences of discrimination compared to the majority in the USA (e.g., Le et al, 2022, Shah et al, 2021, Strassle et al, 2022, & Tan & Umamaheswar, 2021. For instance, ethnic minorities such as Blacks and South Asians in the USA reported similar narratives where they felt that they were stigmatized by the public and the community around them such as, "I think somehow there's always this narrative that we're the other…We have COVID, and nobody else seems to have it.…”
Section: Miconi Et Al (2021a)mentioning
confidence: 99%